A Novel Variation in the Mitochondrial Complex I Assembly Factor NDUFAF5 Causes Isolated Bilateral Striatal Necrosis in Childhood - Bi, Hongyan; Guo, Hui; Wang, Qianfei; Zhang, Xiao; Zhao, Yaming; Li, Jimei; Zhao, Weiqin; Tuo, Houzhen; Zhang, Yongbo (Frontiers in Neurology, 2021)
Bilateral striatal necrosis (BSN) is characterized by symmetrical degeneration in the basal ganglia. It is associated with numerous acquired and hereditary neuro-developmental and motor dysfunction-related pathological conditions. BSN results in high morbidity and mortality among infants and children, and its diagnosis is clinically challenging due to several overlapping disease phenotypes. Therefore, a precise genetic diagnosis is urgently needed for accurate genetic counseling and improved prognostic outcomes as well. Objective: To identify novel missense mutations in the NDUFAF5 gene as a cause of childhood BSN in members of a Chinese family and summarize the clinical characteristics of patients with the NDUFAF5 gene mutations. Methods: This study included a large family living in a remote northwestern area of China. Three siblings developed a neurological disorder characterized by generalized dystonia within the first decade of their lives. Cerebral computed tomography (CT) and magnetic resonance imaging (MRI) showed bilateral lesions of the putamen. Biochemical and genetic approaches were used to identify the cause of BSN. Results: Sequence analysis showed no pathogenic variation in PANK2, SLC25A19, SLC19A3, and NUP62 genes and in the entire mitochondrial genome as well. Whole-exome sequencing revealed compound heterozygous mutations consisting of NDUFAF5:c.425A > C(p.E142A) and c.836T > G (p.M279R). The father, a healthy sister, and a healthy brother of the affected siblings carried the c.836T > G mutation, and the mother carried the c.425A > C mutation. These variants were absent in 100 ethnically matched non-BSN controls. In silico analysis demonstrated that the E142A and M279R mutations in NDUFAF5 protein significantly perturbed the normal conformation of the protein due to alterations in the hydrogen bonding patterns around the evolutionarily conserved catalytic domains, leading to its loss of function in the early stage of mitochondrial complex I assembly. Conclusions: We identified a novel compound heterozygous mutation (c.425A > C and c.836T > G) in the NDUFAF5 gene as the potential cause of autosomal recessive childhood BSN, which extended the pathogenic variation spectrum of the NDUFAF5 gene. This study provides substantial evidence for further improvement of genetic counseling and better clinical management of BSN affected individuals.